Oxygen Control Challenge for Advanced Wet Processing. (11th September 2015) - Yoshida, Yukifumi; Otsuji, Masayuki; Takahashi, H.; Snow, Jim; Sebaai, Farid; Holsteyns, Frank; Mertens, Paul W.; Sato, Masanobu; Shirakawa, Hajime; Uchida, H.
Abstract : A control of Dissolved Oxygen (DO) in liquids and oxygen concentration in ambient atmosphere for semiconductor processing is described. The effects of low DO in wet processing for galvanic corrosion and water mark formation were evaluated using various oxygen concentration conditions with HF or HCl mixtures. It was found that the low DO concentration condition (25ppb) prevented the occurrence of defects (voiding, trenching or water marks). The results from processing a device sample showed that low DO concentration condition is required for advanced CMOS processing.